2016
DOI: 10.1007/s11483-016-9429-4
|View full text |Cite
|
Sign up to set email alerts
|

Denaturation and in Vitro Gastric Digestion of Heat-Treated Quinoa Protein Isolates Obtained at Various Extraction pH

Abstract: The aim of this study was to determine the influence of heat processing on denaturation and digestibility properties of protein isolates obtained from sweet quinoa (Chenopodium quinoa Willd) at various extraction pH values (8, 9, 10 and 11). Pretreatment of suspensions of protein isolates at 60, 90 and 120 °C for 30 min led to protein denaturation and aggregation, which was enhanced at higher treatment temperatures. The in vitro gastric digestibility measured during 6 h was lower for protein extracts pre-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 28 publications
(32 reference statements)
6
44
1
Order By: Relevance
“…There were no statistical differences in the final protein extraction yield (PY%) between flours; but for the case of solid yield (SY%), the YQF showed a higher value, indicating that some other compounds (non-protein based) were coextracted during the protein extraction step. Regarding PY%, our results are similar to the reported by Brinegar and Goundan (1993), with 47% of final protein extraction, but lower in comparison with the 74.3% obtained by Avila Ruiz et al (2016) and the 76.3% reached by Guerreo-Ochoa et al (2015) at pH 11 using NaCl (0.1 N). In the production of protein isolates, several parameters such as protein content of the raw material, thermal treatment of the flour, chemical composition, as well as the conditions used during the extraction process can significantly influence production yields.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…There were no statistical differences in the final protein extraction yield (PY%) between flours; but for the case of solid yield (SY%), the YQF showed a higher value, indicating that some other compounds (non-protein based) were coextracted during the protein extraction step. Regarding PY%, our results are similar to the reported by Brinegar and Goundan (1993), with 47% of final protein extraction, but lower in comparison with the 74.3% obtained by Avila Ruiz et al (2016) and the 76.3% reached by Guerreo-Ochoa et al (2015) at pH 11 using NaCl (0.1 N). In the production of protein isolates, several parameters such as protein content of the raw material, thermal treatment of the flour, chemical composition, as well as the conditions used during the extraction process can significantly influence production yields.…”
Section: Resultssupporting
confidence: 84%
“…Lipids are known to diminish protein extraction due to the formation of protein-lipid emulsions, even when lipids are present in low contents. In a study conducted by Ruiz et al (2016), protein isolates were obtained from deffated quinoa of the sweet cultivar Atlas harvested in Santiago, Chile. They described protein extraction yields from 24 to 37% when the procedure was conducted at pH 8 and 11, respectively.…”
Section: Extraction Of Proteins From Bqf and Yqfmentioning
confidence: 99%
“…This could explain the lower protein digestibility obtained with QPI. This effect by aggregation was previously suggested by Opazo-Navarrete et al [20] and Avila et al [31] who found that quinoa protein preheated at 120°C had lower gastric digestibility as a consequence of protein aggregation.…”
Section: Effect Of Protein Concentration Methods and Temperature On Prsupporting
confidence: 75%
“…Furthermore, Xie et al () showed that protein digestibility reached 93% in Gibel carp fed a diet comprising 32% PPC, which is equivalent to that of FM. From these results, the protein digestibility of PPC is not necessarily inferior to that of FM, and the decrease in protein digestibility with increasing PPC concentration observed in our study was probably due to poor PPC processing and heating conditions, since changes in digestibility depend on processing conditions, such as purification, extraction and heating (Ruiz et al, ). This also applies to PPC digestibility; therefore, it seems necessary to develop processing methods that maximize protein digestibility.…”
Section: Discussionsupporting
confidence: 52%